Β-arrestin–based biosensors: Tools to explore structural determinants of metabolic functions?. (February 2021) - Matthees, Edda Sofie Fabienne; Haider, Raphael Silvanus; Hoffmann, Carsten
Abstract: The arrestin family of proteins is known to regulate receptor desensitization and trafficking of cell surface receptors, especially G protein–coupled receptors. While several physiological processes have been linked to arrestins, the mechanism of action is not always clear. Because arrestins can act as scaffolding proteins, they offer a platform to influence several signaling pathways in different manners. In this review, we first highlight recent studies investigating metabolic functions associated with members of the arrestin family. Next, current breakthroughs in structural studies of G protein–coupled receptor––β-arrestin complexes will be discussed to elaborate on the conformational determinants of arrestin functions. Finally, we review concepts and limitations of arrestin-based sensors to study arrestin functions in living cells and how they might help to enhance our understanding of arrestin biology.